1974
DOI: 10.1083/jcb.62.1.66
|View full text |Cite
|
Sign up to set email alerts
|

DEMONSTRATION OF A FIBRILLAR COMPONENT IN THE CELL WALL OF THE YEAST SACCHAROMYCES CEREVISIAE AND ITS CHEMICAL NATURE

Abstract: The ultrastructure of isolated cell walls of Saccharomyces cerevisiae from the log and stationary phases of growth was studied after treatment with the following enzymes: purified endo-3-(1 -~ 3)-glucanase and endo-3-(l -~ 6)-glucanase produced by Bacillus circulans; purified exo-3-glucanase and endo-3-(1 ~ 3)-glucanase produced by Schizosaccharomyces versatilis; commercial Pronase. While exo-3-glucanase from S. versatilis had no electron microscopically detectable effect on the walls, Pronase removed part of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 16 publications
3
46
1
1
Order By: Relevance
“…5d-f), which differed from the WT cell walls isolated by cell disruption using ballotini. The WT cells retained their ovoid shape (Kopecká et al, 1974). This indicated that the rigidity of the cell walls in the LA-inhibited cells had been affected.…”
Section: Scanning Electron Microscopy Of La Treated Cellsmentioning
confidence: 75%
See 2 more Smart Citations
“…5d-f), which differed from the WT cell walls isolated by cell disruption using ballotini. The WT cells retained their ovoid shape (Kopecká et al, 1974). This indicated that the rigidity of the cell walls in the LA-inhibited cells had been affected.…”
Section: Scanning Electron Microscopy Of La Treated Cellsmentioning
confidence: 75%
“…2f) and buds ( Fig. 2g) of b-1,3-glucan microfibrils (Kopecká et al, 1974). A few cell wall ridges and plasma membrane invaginations ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The innermost layer is predominantly composed of microfibrils of beta-(1,3)-glucan with some beta-(1,6) branch points (143,152,153), while the outer layer is essentially all mannoprotein (9,104). In contrast to the cell walls of most medically important fungi, the cell wall of S. cerevisiae is relatively poor in chitin and depends on the beta-(1,3)-glucan for maintenance of its structural integrity (148).…”
Section: Yeastsmentioning
confidence: 99%
“…Microfibrils of p-(1+3)-glucan make up the wall fibrillar skeleton (Kopecki et al, 1974;.Houwink & Kreger, 1953), which is masked with amorphous P-glucans (Kopecka et al, 1974) and mannoproteins (cf. Bacon, 1981;Kopecka, 1985).…”
Section: Introductionmentioning
confidence: 99%